Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1075/gest.20028.kan
|View full text |Cite
|
Sign up to set email alerts
|

High verbal working memory load impairs gesture-speech integration

Abstract: While previous studies have shown the importance of visuo-spatial working memory in the processing of co-speech iconic gestures, clear evidence for a potential involvement of the verbal working memory (vWM) is currently lacking. To address this issue, participants in the present study were presented with a dual task paradigm. The main outcome variable was the performance on a Stroop-like gesture task which provides a behavioural index of gesture-speec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Additionally, several such studies have failed to observe an overt effect of verbal WM on gesture processing, sometimes despite a clear effect of visuospatial WM on performance. For example, Wu and Coulson (2014a) did not find speech–gesture congruency benefits to be correlated with verbal WM (cf., Kandana Arachchige et al, 2022). In contrast, research from the same group reported ERP changes to comprehension as a function of WM load (Momsen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, several such studies have failed to observe an overt effect of verbal WM on gesture processing, sometimes despite a clear effect of visuospatial WM on performance. For example, Wu and Coulson (2014a) did not find speech–gesture congruency benefits to be correlated with verbal WM (cf., Kandana Arachchige et al, 2022). In contrast, research from the same group reported ERP changes to comprehension as a function of WM load (Momsen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Aldugom et al (2020) found that visuospatial, but not verbal, WM scores were predictive of how much individuals benefited from deictic gestures during math instructions. But what about studies that did find a relation between verbal WM and gesture processing (Kandana Arachchige et al, 2022; Momsen et al, 2020; Schubotz et al, 2021)? There are several points to note here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, in some studies, for example, Schubotz et al (2021), speech was distorted, thus creating greater work for the verbal system to extract the signal, which may exaggerate the role of verbal WM in comprehension. Second, many studies include dual tasking (e.g., Kandana Arachchige et al, 2022;Momsen et al, 2020), which presents a special situation. Additionally, several such studies have failed to observe an overt effect of verbal WM on gesture processing, sometimes despite a clear effect of visuospatial WM on performance.…”
Section: Discussionmentioning
confidence: 99%